Effects of Malassezia globosa on the Expression of Thymic Stromal Lymphopoietin and Differentiation of T Helper Cells in MC903-Induced Atopic Dermatitis Mouse Model - Xin Zhou; Zhuanggui Cheng; Qintai Yang; Han Ma; Yang Xie; Zhe Xu; Jun Xia; Jian Chen; Chun Lu; Peiying Feng (International Journal of Microbiology)
Atopic dermatitis (AD) is a chronic and inflammatory disease with an immunogenetic basis that can be triggered by extrinsic and intrinsic factors, including dysbiosis of the skin microbiota. The lipophilic Malassezia globosa is one of the dominant fungal species on the skin of AD patients. Malassezia and the host pathophysiologic mechanism underlying its role in exacerbating AD symptoms remain to be elucidated. This experiment established a fungal overgrowth model by topical administration suspension of M. globosa on BALB/c mice (M group) and MC903-induced AD model (AD+M group). Our results suggested that more severe AD-like lesions and higher dermatitis scoring were observed in the AD+M group compared with the AD group. The expression of TSLP mRNA in the tissue and serum IgE were highly increased in the AD group, while decreased significantly in the AD+M group. The expression levels of IL-17A and IL-22 in ear tissues and serum were significantly increased with M. globosa stimulation, especially in the AD+M group. Meanwhile, the percentage of Th17 and Th22 cells in the spleen were positively correlated with IL-17A and IL-22 levels in the serum. In contrast, IFN-γ and IL-4 production were significantly decreased in the AD+M group compared with the AD group. This study demonstrated that overgrowing M. globosa could aggravate AD symptoms and that IL-17A and IL-22 may be involved in the process. The promotion of IL-17A and IL-22 production induced by M. globosa may restrain the development of TSLP and inhibit the Th1/Th2 type skin inflammation.